FEMINISM PERSPECTIVE IN A GOOD GIRL’S GUIDE TO MURDER BY HOLLY JACKSON - Putri, Angela Aprilyani; Restu Arini (Journal of Innovation Research and Knowledge, 2024)
Feminism becomes a movement that emerged as a resistance to the dominant treatment that oppressed women due to a patriarchal culture in society and literary works. This study aims to find out the types of feminism portrayed by Pippa Fitz-Amobi in the novel A Good Girl’s Guide to Murder by Holly Jackson. This study uses the theory of Rosemarie Tong, which categorizes feminism into different categories, including liberal and radical feminism. The research method used is a qualitative descriptive method in analyzing data. The data used in this study were obtained from relevant terms, conversations, and statements made by Pippa in the novel through her actions and dialogues. The result of this study reflects the aspects of liberal and radical feminism on Pippa. Liberal feminism highlights equality in education and liberty where Pippa's ambitions and desires are not hindered by patriarchy. For radical feminism, Pippa portrays radical libertarian and radical cultural feminisms.